Fires of St. John: A Drama in Four Acts - Sudermann, Hermann, 1857-1928; Swickard, Charles (Salt Lake City, UT : Project Gutenberg, 2010)
"Fires of St. John: A Drama in Four Acts" by Hermann Sudermann is a dramatic play written in the early 20th century. Set in a country estate in Pomerania, the story revolves around familial relationships and personal struggles, particularly focusing on Gertrude, who is about to marry George, amidst complexities involving Marie, a foundling with a mysterious past. The narrative explores themes such as love, identity, and the societal expectations of marriage. At the start of the play, we are introduced to the Brauer family during a breakfast scene, characterized by lively exchanges and hints of underlying tensions. Gertrude is preparing for her upcoming marriage, while Marie, the adopted daughter, juggles her duties and troubled feelings about her origins. The reappearance of Gertrude's biological mother, a beggar whom the family had previously tried to distance themselves from, creates a sense of impending conflict. This opening not only sets the tone for familial dynamics but also foreshadows deeper explorations of love and duty, culminating in the complex relationships that will unfold as St. John's Eve approaches. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Fires_of_St._John
Release date is 2010-11-18
Produced by Charles Bowen, from page scans provided by Google Books
Keywords: German drama -- Translations into English